Automatic Street Lighting System Using Light Sensor Based on Microcontroller - Samsu Tuwongkesong; Gabriel Sandy Dolang; Ilham Dwika Fadl; Adrian Alexsander Lahengko; Fabio Canavaro Matthew Pangalila (Publikasi Indonesia, 2026)
Street lighting systems play an important role in ensuring the safety, comfort, and security of road users during nighttime. However, manual operation of street lamps often leads to excessive energy consumption due to irregular switching. This research aims to design and implement an automated street lighting system using a light sensor and microcontroller so that lamps can turn on and off automatically according to environmental light intensity. The design process involved hardware design, software development, and system testing under various lighting conditions. The test results showed that the system accurately detected changes in light intensity and controlled the lamps automatically with a fast response time of 0.6 seconds on average. The implementation of this system provides significant energy efficiency of approximately 25–30% reduction in energy consumption. The automatic system based on light sensors and microcontroller can be an effective solution to increase energy efficiency in street lighting infrastructure and serves as a foundation for advanced smart lighting technologies.